Financial burden faced by families due to out-of-pocket expenses during the treatment of their cancer children: An Indian perspective - Latha M Sneha; Jeyanth Sai; S Ashwini; Sunitha Ramaswamy; Mahalakshmi Rajan; Julius X Scott (Indian Journal of Medical and Paediatric Oncology)
Context: Life-saving cancer therapy is costly and may result in financial burden for these families. Financial costs for treating childhood cancer care are traditionally assessed based on the amount spent for diagnostic tests, hospitalization, and chemotherapy. The financial costs for travel, accommodation, out-of-pocket expenses for food, phone bills, and loss of income due to reduction or termination of parental employment are hidden nonmedical expenses that are rarely accounted for. Studies on the financial implications of pediatric cancer treatment are based on the Western model of healthcare with good government/state insurance coverage and hence literature on lifestyle implications for families in developing nations with limited resources is still scarce. Aims: The aim of this study is to find out the details of out-of-pocket expenses incurred by the families during their treatment of cancer children and its implications on their quality of life. Settings and Design: This study was conducted in a tertiary care center for pediatric malignancies for over 1-year period. Subjects and Methods: About seventy families whose children were diagnosed with acute leukemia and undergoing treatment at our center were asked to fill a questionnaire detailing their out-of-pocket expenses. Results: Nonmedical expenses accounts for about 46% of their monthly household income of parents from rural areas and 22% of their household income from urban areas. On an average, a family from rural area spends four times the normal amount spent on home for their daily food expenditure. Thirty-eight percent of families have borrowed money from money lenders with an average interest rate of about 12.5% which pushes them to a state of debt for the next few years. Conclusions: Out-of-pocket expenses contribute a significant proportion to the financial burden of the families with childhood malignancies and these invisible expenses should be recognized and provide adequate support to lessen the burden of this economic impact.